The Likelihood of Resistant Tinea Capitis Caused by Hortaea Werneckii: A Case Report - Zheng W; Zhang M; Wu W; Tang X; Pan Z (Clinical, Cosmetic and Investigational Dermatology)
Wenai Zheng,1 Ming Zhang,2 Weiwei Wu,2 Xiaozheng Tang,1 Zhaobing Pan2 1Department of Clinical Laboratory, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, 570206, People’s Republic of China; 2Department of Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, 570206, People’s Republic of ChinaCorrespondence: Xiaozheng Tang; Zhaobing Pan, Email 415687035@qq.com; panzhaobing0108@163.comAbstract: This case study illustrates a 24-year-old Chinese man who presented with tinea capitis associated with a fungal infection. He was administered a therapeutic regimen consisting of terbinafine, ketoconazole cream, and miconazole shampoo for 2 months. However, the symptoms recurred 3 months after the treatment ended. Fungal culture and sequencing confirmed the infection of Hortaea werneckii. Drug sensitivity testing showed that the infecting strain of the patient remained sensitive to the five commonly used antifungal drugs in vitro. While most cases infected by Hortaea werneckii present with Tinea nigra, the possibility of Hortaea werneckii infection should be considered in patients with tinea capitis living in coastal cities.Keywords: fungal infection, immunofluorescent staining, sequencing, treatment